2014
DOI: 10.1080/09205063.2013.879561
|View full text |Cite
|
Sign up to set email alerts
|

Micro-structuring of polycarbonate-urethane surfaces in order to reduce platelet activation and adhesion

Abstract: In the development of new hemocompatible biomaterials, surface modification appears to be a suitable method in order to reduce the thrombogenetic potential of such materials. In this study, polycarbonate-urethane (PCU) tubes with different surface microstructures to be used for aortic heart valve models were investigated with regard to the thrombogenicity. The surface structures were produced by using a centrifugal casting process for manufacturing PCU tubes with defined casting mold surfaces which are conferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
4
11
0
Order By: Relevance
“…2C). This is in agreement to the literature thresholds for structure dimensions which have a negative impact on the hemocompatibility of the surface (3,18,21).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…2C). This is in agreement to the literature thresholds for structure dimensions which have a negative impact on the hemocompatibility of the surface (3,18,21).…”
Section: Resultssupporting
confidence: 92%
“…The chemical methods include all modifications of the material's chemistry as, for example, organic and inorganic coatings or bio-functionalization (9)(10)(11)(12)(13). Physical methods include all techniques which alter the surface properties by mechanical structuring of the surfaces, for example, random or regular structures in the micro-or nanometer range or the adjustment of a special roughness (3,7,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Ding et al…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Recently, topographic approaches for controlling biological response have become increasingly common. 6,15 Numerous studies have demonstrated that micro-or nanostructured surfaces influence cell behaviors, 21,22 reduce platelet adhesion/activation, 23,24 and inhibit bacterial adhesion/ biofilm formation. [25][26][27][28][29] Among them, the ability to inhibit bacterial adhesion through topographic approach might be more attractive since the topographic approach does not require incorporating antibiotic agents into materials that might lead to antibiotic resistance of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The surface roughness reported here may be mitigated by refining the manufacturing process. 68 Platelet adhesion on other valve polymer candidates (such as thermoplastic polyurethane, PCU, and silicone) has been reduced by surface smoothing of thermoplastic polyurethane with Argon plasma treatment, 69 transfer of a wave-like groove pattern to PCU tubes from a centrifugal casting mold, 70 and magnetic abrasive finishing of silicone rubber. 71 Optimization of xSIBS roughness using similar techniques will be explored in the future.…”
Section: Discussionmentioning
confidence: 99%